Does An Innovation’s Reach Reveal Anything About Its Impact? Under The Right Conditions: Possibly - Brooks, Matt; Lybbert, Travis J.; Walker, Madeleine (CGIAR Standing Panel on Impact Assessment, 2025)
Impact—the extent to which a specific innovation causally affects a target outcome—is an ideal measure of a program’s success. However, impact evaluations are time- and resource-intensive, making them unavailable in many circumstances. By contrast, measuring the reach of an innovation, i.e., the number of adopters, is more straightforward. As a result, measures of reach are more prevalent than causal impact estimates.